AUDITOR HUKUM DI ERA DIGITALISASI DALAM UPAYA MENCEGAH TRANSAKSI TINDAK PIDANA PENCUCIAN UANG - Urbanisasi Urbanisasi (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2019)
One of the legal auditors in Indonesia is the Center for Financial Transaction Reports and Analysis. In Law 8 of 2010 concerning the Prevention and Eradication of the Crime of Laundering, it expressly mandates the establishment of the Financial Transaction Reports and Analysis Center (PPATK) as a central institution (focal point) which Numbers the Implementation of the Act in order to prevent and criminal actor money laundering. in Indonesia. The problem is how are legal auditors in the digitalization era in an effort to prevent money laundering. The research method used is normative juridical research. The results of the research are that the existence of a legal auditor is one of the efforts to prevent money laundering crimes, where it is necessary to search for assets resulting from criminal acts, which are generally carried out by financial institutions through mechanisms regulated in laws and regulations. PPATK may cooperate in exchanging information in the form of requesting, giving, and receiving information with parties, both nationally and internationally.